2022
DOI: 10.55218/jasr.202213507
|View full text |Cite
|
Sign up to set email alerts
|

NATURAL DYE SENSITIZED SOLAR CELLS USING HENNA LEAVES WITH ZnO NANOPARTICLE AT VARIOUS pH VALUES

Abstract: In this research, ZnO nanoparticles were synthesized at different pH values (3, 6 and 9) by using solvothermal method. To our knowledge, dye sensitized solar cells were fabricated using natural dyes extracted from henna (Lawsonia Inermis) based on ZnO nanoparticle as photoanode at various pH values. Synthesized ZnO samples were characterized using XRay Diffraction (XRD), Field Emission Scanning Electron Microscope (FESEM) with Energy Dispersive X-ray Spectroscopy (EDX), UV-Visible Spectroscopy and Fourier Tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…It was demonstrated that the efficiency of ZnO nanorod solar cells sensitized with HE surpassed that of solar cells sensitized with beetroot and amla extracts. Esakki et al ( 2022 ) engineered DSSCs using colors derived from henna, applying the solvothermal technique at different pH levels (3–9), and utilizing ZnONPs created with HLE as a photoanode. The ZnONPs achieved the highest efficiency of 0.39% at pH 9, outperforming other solar cells.…”
Section: Dye-sensitized Solar Cellsmentioning
confidence: 99%
“…It was demonstrated that the efficiency of ZnO nanorod solar cells sensitized with HE surpassed that of solar cells sensitized with beetroot and amla extracts. Esakki et al ( 2022 ) engineered DSSCs using colors derived from henna, applying the solvothermal technique at different pH levels (3–9), and utilizing ZnONPs created with HLE as a photoanode. The ZnONPs achieved the highest efficiency of 0.39% at pH 9, outperforming other solar cells.…”
Section: Dye-sensitized Solar Cellsmentioning
confidence: 99%